Palliative pelvic radiotherapy for symptomatic incurable prostate cancer – A prospective multicenter study. Issue 3 (June 2015) - Cameron, Marte Grønlie; Kersten, Christian; Vistad, Ingvild; van Helvoirt, Rene; Weyde, Kjetil; Undseth, Christine; Mjaaland, Ingvil; Skovlund, Eva; Fosså, Sophie D.; Guren, Marianne Grønlie
Abstract Background and purpose Radiotherapy is used to palliate pelvic symptoms of castration resistant prostate cancer (CRPC). However, magnitude and time course of effects and toxicities are poorly documented. Study aims were to evaluate changes in patient-reported target symptoms (TS), health-related quality of life (HRQOL) and toxicity following palliative pelvic radiotherapy (PPRT) of CRPC. Material and methods 47 patients with CRPC and a symptomatic pelvic mass prescribed PPRT with 30–39 Gy were prospectively included. Primary endpoint was patient-reported improvement or complete resolution of the TS twelve weeks after PPRT. HRQOL changes were explored. Toxicity was physician-evaluated. Results Lower urinary tract symptoms (LUTS) (45%), hematuria (26%) and pain (19%) were the most common TS. In the 40 evaluable patients, overall TS response twelve weeks after PPRT was 70%. TS responses were 8/18 for LUTS, 11/12 for hematuria, and 7/9 for pain. Global HRQOL improved transiently. The most common toxicity was grade 1 or 2 diarrhea (50%). There was no grade 4 toxicity. Conclusions In the majority of patients with CRPC and a symptomatic pelvic tumor, PPRT with 30–39 Gy contributes to relief of hematuria, pain and other pelvic symptoms, with acceptable toxicity. Future studies should investigate whether PPRT regimens can be simplified.